Another dynamic model of Markovian human-machine-environment system affected by some hazard - Naumeyko, I. V.; Alazawi, R. J. (ХНУРЭ, 2013)
The problem of modeling the behavior of a system and operator, both effected by some hazard is discussed. The cases are considered, when the flow of events generated by the subsystems "machine" and "environment" is the simplest, and also the case when the intensity of the flow is possible to approximate by a flow of Erlang, and when the intensity changes in time.